Empowerment Approachas A Stunting Prevention Intervention: Scoping Review - Ratna Trisilawati; Zahroh Shaluhiyah; Bagoes Widjanarko (Universitas Aisyah Pringsewu, 2022)
Stunting is a cumulative reflection of chronic nutrition, infection, and other factors that occur from time to time and cause health problems and poor child development, and can endanger the quality of life of future generations of a nation. Interventions to overcome the problem of stunting have been carried out in various ways, both specifically and sensitively. Stunting is still a global issue, and various interventions have been carried out to overcome it, one of which is the empowerment approach which is an important principle to improve the quality of life. This study is a scoping review that contains literature on empowerment as a stunting prevention intervention. Article searches are carried out using online databases such as Google Scholar, PubMed, and Proquest. PRISMA flow chart was used for selection. The search results yielded 4,419 literature, title screening rejected 1,648 kinds of literature, and 115 items screened full text, with 12 kinds of literature meeting the inclusion requirements. The empowerment approach that is often carried out is women's empowerment, but in stunting prevention interventions, women's empowerment approaches are not enough to require other empowerment efforts such as empowering cadres as well as families and communities. The involvement of the community’s active role is necessary to prevent stunting because the community is the front line and understands the problems that occur in their respective regions, so the concept of the approach top-down and bottom-up must work well together. Joint efforts are needed in preventing stunting, one of which is the empowerment that is not only focused on empowering women but can also be empowered cadres, families, and communities. In determining empowerment indicators, it is hoped that it will not be too broad because the indicators, domains, and questions used in a study aimed to measure empowerment or in developing an empowerment index. Abstrak: Stunting adalah cerminan kumulatif dari gizi kronis, infeksi, dan faktor lain yang terjadi dari waktu ke waktu dan menjadikan masalah kesehatan serta tumbuh kembang anak yang buruk, serta dapat membahayakan kualitas hidup generasi masa depan suatu bangsa. Stunting masih menjadi isu dunia, dan berbagai intervensi telah dilakukan untuk mengatasinya, salah satunya dengan pendekatan pemberdayaan yang merupakan prinsip penting untuk meningkatkan kualitas hidup. Kajian ini merupakan scoping review yang memuat literatur tentang pemberdayaan sebagai intervensi pencegahan stunting. Pencarian artikel dilakukan dengan memanfaatkan database online seperti Google Scholar, PubMed, dan Proquest. Diagram alir PRISMA digunakan untuk seleksi. Hasil pencarian menghasilkan 4.419 literatur, penyaringan judul ditolak 1.648 literatur dan 115 item disaring teks lengkap, dengan 12 literatur memenuhi persyaratan inklusi. Pendekatan pemberdayaan yang seringkali dilakukan adalah pemberdayaan perempuan, tetapi dalam intervensi pencegahan stunting pendekatan pemberdayaan perempuan saja tidak cukup perlu upaya pemberdayaan lainnya seperti pemberdayaan kader maupun keluarga serta masyarakat. Pelibatan peran aktif masyarakat sangat diperlukan sebagai upaya pencegahan stunting, karena masyarakat adalah garda terdepan dan memahami masalah yang terjadi diwilayah masing-masing, sehingga konsep pendekatan topdown dan bottom up haruslah bersinergi dengan baik. Perlu upaya bersama dalam pencegahan stunting salah satunya dengan pemberdayaan yang tidak hanya difokuskan kepada pemberdayaan perempuan saja tetapi dapat juga dilakukan pemberdayaan kepada kader, keluarga maupun masyarakat. Dalam penentuan indikator pemberdayaan diharapkan tidak terlalu luas karena indikator, domain dan pertanyaan yang digunakan didalam sebuah penelitian bertujuan untuk mengukur pemberdayaan atau dalam pengembangan indeks pemberdayaan.